Effect of DA‐9701, a novel prokinetic agent, on stress‐induced delayed gastric emptying and hormonal changes in rats. Issue 3 (6th December 2012) - Jung, Y.‐S.; Kim, M.‐Y.; Lee, H. S.; Park, S. L.; Lee, K. J.
Abstract Background DA‐9701 is a novel prokinetic agent formulated with Pharbitis Semen and Corydalis Tuber. This study aimed to evaluate the effect of DA‐9701 on stress‐induced delay in gastric emptying and changes in plasma adrenocorticotropic hormone and ghrelin levels in rats. Methods Changes in gastric emptying in response to different durations of stress were evaluated. Gastric emptying was compared between the following groups: (i) nonstressed vehicle‐ or DA‐9701‐treated group, (ii) nonstressed vehicle‐ or mosapride‐treated group, (iii) 2‐h stressed vehicle‐ or DA‐9701‐treated group, and (iv) 2‐h stressed vehicle‐ or mosapride‐treated group. Water immersion restraint stress was used as the stressor. DA‐9701 or mosapride at 3 mg kg−1 was administered to the rats after subjecting them to 2‐h stress, and then gastric emptying was measured using the phenol red method. Key Results Gastric emptying was significantly delayed in the 2‐h stressed group compared with the nonstressed group. Mosapride administration resulted in significant recovery from the stress‐induced delay in gastric emptying. Gastric emptying in the rats that underwent 2‐h stress followed by DA‐9701 administration was not significantly different from that in the nonstressed group. The plasma adrenocorticotropic hormone and active ghrelin levels in the 2‐h stressed group were significantly higher than those in the nonstressed group. These increases were significantly inhibited by DA‐9701. Conclusions & Inferences The administration of DA‐9701 improved delayed gastric emptying and inhibited the hormonal changes induced by stress, suggesting that DA‐9701 can be used as a gastroprokinetic agent for the treatment of delayed gastric emptying, particularly that associated with stress.